Study on Salmonella Isolates from Fresh Milk of Dairy Cows in Selected Districts of Wolaita Zone, Southern Ethiopia - Asefa, Isayas; Legabo, Ermias; Wolde, Tsegaye; Fesseha, Haben (International Journal of Microbiology, 2023)
Salmonella infections are most commonly found in animal-derived foods. From December 2021 to May 2022, the researchers conducted a cross-sectional study to determine the prevalence of Salmonella isolated from raw milk collected in and around Areka town, Boloso Sore Woreda, Wolaita Zone, Southern Ethiopia. A total of 151 direct udder milk samples were collected at random and examined using bacteriological methods. The overall prevalence of Salmonella was 9.3% (14/151). Breed, age, body condition, lactation stage, and parity were statistically significant risk factors (p<0.05). Salmonellosis was more common and statistically significant in dairy cows with poor body condition and late lactation stage, as well as the Holstein Friesian crossbreed, accounting for 17.6%, 19.1%, and 17.3%, respectively. The farm’s husbandry hygiene and management system, on the other hand, had no significant association with salmonellosis (p>0.05). Salmonellosis was generally considered to be moderately prevalent and was one of the diseases of dairy cows in the study area that could have an impact on dairy production and have serious health and financial repercussions. As a result, improvements in milk quality maintenance and assurance are encouraged, and the need for additional research in the study area was suggested along with other ideas.